YOUNG MOTHER PSICHOPRENEUR SCHOOL : PENDAMPINGAN PSIKIS DAN KEWIRAUSAHAAN IBU MUDA KORBAN PERNIKAHAN DINI BERBASIS KOMUNITAS TERINTEGRASI - Suci Putrid Astiti (AN-NISA, 2018)
The phenomenon of early marriage results in a variety of problems, one of which is the economic problems caused by dropping out of school. Based on data from the Central Bureau of Statistics (BPS), 94.72% of early married children drop out while only 11.54 are married % passed high school level, in other words the early marriage actors had a low quality of Human Resources (HR), while from various studies said poverty occurred due to a lack of quality human resources. To cover up the problem, Young mother psychiatric school was present to provide entrepreneurial counseling assistance to young mothers. Starting with program design which included determining the location of assistance in each region, program budgeting, determination of entrepreneurial counselors, exploration of regional business potential, and program socialization to the community. In its implementation, there are five programs that will be implemented, namely sharing class (psychological and family economic counseling), "business from the environment" class explores the business potential that exists in the surrounding environment, product making, community marketing and regeneration to continue piloting young mothers to become more independent. Next will be an evaluation of the advantages and disadvantages of the program as an improvement material.